The Influence Of Information Technology On The Knowledge Management Process - Wei, Chong Chin; Yeganeh, Mehran (Journal of Knowledge Management Practice, 2013)
Due to rapid development of knowledge management and information technology, business environments have become more competitive. Knowledge is increasingly being recognized as a vital organizational resource that provides competitive advantage; IT can help a company’s aiming to gain a competitive advantage. The role of information technology in knowledge management is an essential consideration for any company wishing to exploit emerging technologies to manage their knowledge assets. This paper examines the influence of IT tools, technology, organization information, IT accessibility for employee, IT supports, IT skill, and IT infrastructure and investment on knowledge management process .The survey questionnaires were distributed to the IT department employees in MSC Malaysia world class companies in Klang valley. The finding of the study and data analysis indicates that all the IT elements except IT supports have positive relationship with knowledge management process. Although many organizations have practices KM in their organizations, there is a need to develop a proper IT model in KM implementation. The present study would be valuable to industrial practitioners because the proposed model can serve as a practical assessment for measuring the IT factors KM implementation